What would you like to achieve?: goal-setting in patients with dementia in geriatric rehabilitation - Dutzi, Ilona; Schwenk, Michael; Kirchner, Marietta; Bauer, Jürgen M.; Hauer, Klaus (BMC geriatrics, 2019)
Setting meaningful, individualized rehabilitation goals is an essential part of the rehabilitation process. Even though patients with dementia are a drastically increasing patient group in geriatric rehabilitation, empirical data about meaningful rehabilitation goals and collaborative goal-setting in this target group is missing. Cognitive impairment and lack of insight in current deficits have been discussed as barriers for participation in goal-setting, but require empirical examination.